Use of Epivolve phage display to generate a monoclonal antibody with opsonic activity directed against a subdominant epitope on extracellular loop 4 of Treponema pallidum BamA (TP0326) - Ferguson, Mary R.; Delgado, Kristina N.; McBride, Shannon; Orbe, Isabel C.; La Vake, Carson J.; Caimano, Melissa J.; Mendez, Qiana; Moraes, Trevor F.; Schryvers, Anthony B.; Moody, M. Anthony; Radolf, Justin D.; Weiner, Michael P.; et al. (Frontiers in Immunology, 2023)
Introduction Syphilis, a sexually transmitted infection caused by the spirochete Treponema pallidum (Tp), is resurging globally. Tp’s repertoire of outer membrane proteins (OMPs) includes BamA (β-barrel assembly machinery subunit A/TP0326), a bipartite protein consisting of a 16-stranded β-barrel with nine extracellular loops (ECLs) and five periplasmic POTRA (polypeptide transport-associated) domains. BamA ECL4 antisera promotes internalization of Tp by rabbit peritoneal macrophages. Methods Three overlapping BamA ECL4 peptides and a two-stage, phage display strategy, termed “Epivolve” (for epitope evolution) were employed to generate single-chain variable fragments (scFvs). Additionally, antisera generated by immunizing mice and rabbits with BamA ECL4 displayed by a Pyrococcus furiosus thioredoxin scaffold (PfTrxBamA/ECL4). MAbs and antisera reactivities were evaluated by immunoblotting and ELISA. A comparison of murine and rabbit opsonophagocytosis assays was conducted to evaluate the functional ability of the Abs (e.g., opsonization) and validate the mouse assay. Sera from Tp-infected mice (MSS) and rabbits (IRS) were evaluated for ECL4-specific Abs using PfTrxBamA/ECL4 and overlapping ECL4 peptides in immunoblotting and ELISA assays. Results Each of the five mAbs demonstrated reactivity by immunoblotting and ELISA to nanogram amounts of PfTrxBamA/ECL4. One mAb, containing a unique amino acid sequence in both the light and heavy chains, showed activity in the murine opsonophagocytosis assay. Mice and rabbits hyperimmunized with PfTrxBamA/ECL4 produced opsonic antisera that strongly recognized the ECL presented in a heterologous scaffold and overlapping ECL4 peptides, including S2. In contrast, Abs generated during Tp infection of mice and rabbits poorly recognized the peptides, indicating that S2 contains a subdominant epitope. Discussion Epivolve produced mAbs target subdominant opsonic epitopes in BamA ECL4, a top syphilis vaccine candidate. The murine opsonophagocytosis assay can serve as an alternative model to investigate the opsonic potential of vaccinogens. Detailed characterization of BamA ECL4-specific Abs provided a means to dissect Ab responses elicited by Tp infection.